Distribution of ABO blood groups and Rh(D) factor in and around Anatapuramu, Andhra Pradesh - C Bhavani; Swapna R.Sujeeva; Neeraja M.; P. Sravani; B. Chaitanya (International Journal of Medical Research and Review, 2016)
Background: India is a vast country with lot of diversity in race, religion and creed. The same diversity has been observed in geographical distribution of blood groups in population within country. ABO and Rh blood groups are most important blood groups in human beings. Objectives: A retrospective study was conducted at Government Medical College/ Government General Hospital Blood Bank Anantapuramu over a period of one year from January 2014 to December 2014 to determine and compare the distribution of ABO and Rh blood groups.Materials and Methods: A retrospective study of one year was carried out at our blood bank in Government Medical College & Hospital, Anantapuramu in Andhra Pradesh, South India. Data pertaining to the blood groups of donors was collected from the Blood Bank donor register from January 2014 to December 2014.Results: The total donors studied from January 2014 to December 2014 were 6942. The distribution of blood groups was : blood group ‘A’ 1386 ( 20 % ), ‘B‘ 2489 ( 35.8 % ), ‘AB’ 509 ( 7.3 % ) and ‘ O ‘ 2558 ( 36.9 % ). In both Rh D positive and Rh D negative person’s blood group ‘ O ‘ was the commonest followed by blood group ‘ B ‘ Blood group ‘ AB ‘ is the least common.Conclusion: The “O” blood group is significantly high in our population and comparatively low “AB” blood group. Every transfusion center should have a record of frequency of blood group system in their population. The study of distribution of blood group is very important for blood banks and transfusion services that could contribute to the patients’ health care.